Influência da terapia fotodinâmica no processo de descontaminação de canais radiculares preparados com diferentes concentrações de soluções de hipoclorito e sistema reciprocante - estudo in vitro - Dias, Caroline Tumelero (2018)
The main goal of endodontic therapy is to perform adequate shaping and cleaning by using instruments and antibacterial protocols. Thus, the aim of this study is to evaluate the antimicrobial activity of hypochlorite solutions and reciprocating instrumentation associated with photodynamic therapy (PDT). Methods: One hundred and twenty root canals were enlarged up to #45 K-file and inoculated with E. faecalis for 14 days. One hundred samples were randomly divided into ten groups (n=10) and subjected to the following protocols: G1-distilled water + Reciproc R40 (control), G2-1% sodium hypochlorite (NaOCl) + Reciproc R40, G3-2.5% NaOCl + Reciproc R40; G4-1% calcium hypochlorite (Ca[OCl]2) + Reciproc R40, G5-2.5% Ca(OCl)2 + Reciproc R40; G6-PDT; G7-1% NaOCl + Reciproc R40 + PDT, G8-2.5% NaOCl + Reciproc R40 + PDT; G9-1% Ca(OCl)2 + Reciproc R40 + PDT, G10-2.5% Ca(OCl)2 + Reciproc R40 + PDT. The percentage bacterial reduction was checked by counting the colonyforming units (CFUs). The remaining 20 samples were subjected to the same decontamination protocols (n = 2) and submitted to scanning electronic microscopy (SEM) to illustrate the effectiveness of the proposed treatments. Data were subjected to one-way ANOVA followed by Tukey’s post hoc test (α = 0.05). Results: The greatest ability to promote bacterial reduction was observed in groups 7 (1% NaOCl + R40 + PDT), 8 (2.5% NaOCl + R40 + PDT), 9 (1% Ca[OCl]2 + R40 + PDT), and 10 (2.5% Ca[OCl]2 + R40 + PDT), with no significant difference between them (p < 0.05). Conclusions: The association of PDT with hypochlorite solutions and reciprocating instrumentation provides effective elimination of E. faecalis.